2020
DOI: 10.3389/fcvm.2020.596921
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Neuroendocrine Tumor With Cardiac Metastasis

Abstract: Neuroendocrine tumors (NETs), also known as carcinoid tumors, are a heterogeneous group of neoplasms that arise from cells throughout the neuroendocrine system, most commonly arising from the gastrointestinal (GI) tract, lungs, and bronchi. Myocardial carcinoid metastasis is rare with an incidence among metastatic carcinoid patients of 4%. They are generally asymptomatic and detected incidentally. Infiltrative myocardial metastasis secondary to carcinoid tumor is exceedingly rare with only single-digit cases r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 8 publications
(7 reference statements)
1
8
0
Order By: Relevance
“…Cardiac metastases from NEN are a relatively rare phenomenon per the literature, with an overall incidence of 4% 10 . Review of the literature showed only three case reports 10–12 and one case series 13 regarding treatment of patients with cardiac metastases secondary to neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cardiac metastases from NEN are a relatively rare phenomenon per the literature, with an overall incidence of 4% 10 . Review of the literature showed only three case reports 10–12 and one case series 13 regarding treatment of patients with cardiac metastases secondary to neuroendocrine tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It is rare to find myocardial metastasis from NEN, with an overall incidence of 4% among metastatic carcinoid patients 10 . Cardiac metastases are typically asymptomatic at presentation and detected incidentally.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cardiac metastasis from primary neuroendocrine tumors is exceedingly rare and usually found incidentally on dotatate imaging (also called octreoscan). The incidence of intracardiac metastasis is approximately 4% in all patients with metastatic carcinoid tumors ( Kinney et al, 2020 ). Nonetheless, the advanced practitioner should rule out infiltrative cardiac metastasis by dotatate imaging as the cause of heart failure in this patient population.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical presentation depends on the site and size of the metastasis. NET with cardiac metastasis is typically asymptomatic from a heart standpoint, but there is a recently reported case 4 where the patient presented with heart failure at the time of diagnosis. Metastasis to the left ventricle accounts for 53% of cases, compared with only 7% of metastasis to the intraventricular septum.…”
Section: Discussionmentioning
confidence: 99%